Análise do DNA mitocondrial como ferramenta para identificação de espécies do subgênero Leishmania Viannia (Lainson & Shaw, 1987) - Isabella Figueiredo de Andrade (2014)
Leishmaniasis is a vectorial chronic disease caused by flagellated protozoa of genus Leishmania (Ross, 1903) which are divided into two subgenera, Leishmania and Viannia. It can be manifested in two major forms: tegumentary and visceral, the latter being divided into cutaneous, disseminated, diffuse and mucocutaneous. The focus of this work was on species that cause cutaneous leishmaniasis of the subgenus Viannia. It is reported in Brazil more than 25.000 cases of tegumentary leishmaniasis each year and it is considered by the World Health Organization one of the six major infectious diseases. Leishmania (Viannia) braziliensis is the main species that causes tegumentary leishmaniasis in Brasil. Currently, the diagnosis methods used in clinical pratical guide are based on immune response (Montenegro intradermal test) and direct microscopic examination of the sample collected from lesion, fixed and Giemsa-stained. Such methods are effective for disease diagnostic but do not allow determining which species is present. The determination of this species is important to determine the prognostic and the best treatment for the disease, since some species respond better to certain drugs and to different amounts of therapy. The identification of species is possible by isoenzyme analysis method, but this technique depends on the culture of parasites isolated from lesion to obtain sufficient amounts of protein, is inclined to contamination by bacteria and yeast, is difficult to interpret and result can lead 3-5 weeks to be available, precluding its clinical use. The search for molecular methodologies involving polymerase chain reaction (PCR) is recent, even those based on mitochondrial DNA (kDNA). The problem for further study of this methodology is lack of kDNA sequences on NCBI GenBank, especially for species of subgenus Viannia. Thus, the aim of our study was to investigate candidate genes to identify species that cause tegumentary leishmaniasis, focusing on subgenus Viannia, and enrich GenBank with new sequences to future studies. We used two approaches. The first aimed to amplify genes: ATPase subunit 6 (ATP6), cytochrome oxidase subunit II (COII), cytochrome oxidase subunit III (COIII) and cytochrome b (Cyt b) of reference species of World Health Organization – WHO strains of subgenus Viannia. The second aimed to amplify the complete coding region of Leishmania (V.) braziliensis strain M2903 maxicircle in order to provide others gene sequences to study. The first part of our work has generated 27 new sequences and all of them were analyzed for presence of polymorphic sites able to identificate species of subgenus Viannia. Cyt b gene was the one that showed to be best candidate for development of a methodology involving allele-specific primers. But more genes must be studied and other strains included in analysis. The second part generated 16 gene sequences of maxicircle kDNA, allowing more genes to be studied about the possibility of becoming targets to species-specific molecular diagnosis